Early-Onset Depression in Stroke Patients: Effects on Unfavorable Outcome 5 Years Post-stroke - Zeng, Ya-Ying; Wu, Meng-Xuan; Zhou, Sheng-Nan; Geng, Dan-Dan; Cheng, Lin; Fan, Kai-Li; Yu, Xin; Tang, Wen-Jie; He, Jin-Cai (Frontiers in Psychiatry, 2021)
Abstract: Background: Post-stoke depression (PSD) constitutes an essential complication of stroke and is associated with high-risk unfavourable outcome after stroke. The main objective of this prospective study was to determine the relationship between early-onset PSD (1 month after stroke) and functional outcomes five years after baseline enrollment. Methods: Four hundred thirty-six patients who met the criteria were included in this study from October 2013 to February 2015. The follow-up time for each patient was approximately 5 years, with follow-up every 3 months. Patients received questionnaires including the 17-item Hamilton Depression Scale (HAMD), the Mini-Mental State Examination (MMSE), the NIH Stroke Scale (NIHSS), the modified Rankin Score (mRS), and the Barthel Index (BI). Results: Of the 436 patients, 154 (35.3%) patients with the prevalence of PSD status at baseline, 26 (7.2%) patients with the prevalence of PSD status, and 73 (20.1%) had a unfavourable outcome 5 years after stroke. The odds ratio (OR) for unfavourable outcome at 5 years in the PSD group was approximately 2.2 relative to the non-PSD group after adjusting for potential risk factors (OR=2.217, 95% CI= 1.179–4.421, P=0.015). In the early-onset PSD group, HAMD scores were independently associated with 5-year unfavourable outcome rates (OR=1.168, 95% CI=1.015-1.345, P=0.031). Conclusions: Our findings indicate that early-onset PSD status in Chinese patients is an independent risk factor for unfavourable outcome 5 years after stroke and that the severity of PSD is also related to unfavourable outcome.